Efficiency of Land Use in Smallholder Palm Oil Plantations in Indonesia: A Stochastic Frontier Approach - Sari, Dyah Wulan; Hidayat, Faqih Nur; Abdul, Irawati (Forest and Society, 2021)
Indonesia has become the country with the largest palm oil production. However, the level of productivity of oil palm per land in Indonesia tends to remain stagnant. The main objective of this study is to evaluate oil palm lands of smallholders that experience land inefficiency. In analyzing land efficiency, this study used cross-section data obtained from Statistics Indonesia (BPS). This study uses an input distance function approach with stochastic frontier analysis tools. Our estimation results found that on average, smallholders oil palm plantations face land inefficiency. The land inefficiency of smallholder oil palm plantations is not proportional to the negative impacts it has caused. The intensification of oil palm plantation land is one of the ways to reduce the rate of deforestation and optimize available land. Land intensification can be done through the selection of potential lands, renewal programs for oil palm trees, supporting facilities and infrastructure, and plantation technology development.